Effects of TAT-conjugated platinum nanoparticles on lifespan of mitochondrial electron transport complex I-deficient Caenorhabditis elegans, nuo-1 - Yuri Sakaue (Dove Medical Press, 2010)
Yuri Sakaue, Juewon Kim, Yusei MiyamotoDepartment of Integrated Biosciences, University of Tokyo, Chiba, JapanAbstract: Platinum nanoparticle (Pt-np) species are superoxide dismutase/catalase mimetics and also have an activity similar to that of mitochondrial electron transport complex I. To examine if this complex I-like activity functions in vivo, we studied the effects of Pt-nps on the lifespan of a mitochondrial complex I-deficient Caenorhabditis elegans mutant, nuo-1 (LB25) compared with wild-type N2. We synthesized a fusion protein of a cell-penetrating peptide, human immunodeficiency virus-1 TAT (48–60), C-terminally linked to a peptide with a high affinity to platinum (GRKKRRQRRRPPQ-DRTSTWR). Pt-nps were functionalized by conjugation with this fusion protein at a 1:1 ratio of TAT-PtBP to Pt atoms. Adult worms were treated with conjugated Pt-nps for 10 days. The mean lifespan of untreated N2 and LB25 was 19.6 ± 0.4 and 11.8 ± 0.3 days, respectively. Using 5 µM of conjugated Pt-nps, the lifespan of N2 and LB25 was maximally extended. This maximal lifespan extension of LB25 was 31.9 ± 2.6%, which was significantly greater than that of N2 (21.1 ± 1.7%, P < 0.05 by Student’s t-test). Internalization of Pt into the whole body and mitochondria was similar between these two strains. Excessive accumulation of reactive oxygen species was not observed in the cytosol or mitochondria of untreated LB25. Treatment for five days with 5 µM conjugated Pt-nps decreased cytosolic and mitochondrial reactive oxygen species in N2 and LB25 to a similar extent. The ratio of [NAD+]/[NADH] was very low in the whole body and mitochondria of control LB25. After five days of treatment with 5 µM conjugated Pt-nps, the ratio of [NAD+]/[NADH] was increased in N2 and LB25. However, the degree of the increase was much higher in LB25 than in N2. Pt-nps function as NADH oxidase and recover the [NAD+]/[NADH] ratio in LB25, leading to effective extension of the lifespan of LB25.Keywords: platinum nanoparticles, Caenorhabditis elegans, complex I-deficient mutant, LB25, lifespan